(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Despite of all successes in commercialization of GaN-based devices present knowledge of light emission mechanisms in these devices is surprisingly limited. In my talk I discussed several puzzling properties of wide band gap nitrides. Some of them are briefly described below. First, I discuss correlations between structural quality of thin films of GaN and their light emission properties. Then, the mechanisms responsible for strong carrier/excitons localization effects are discussed. Finally, I discuss properties of n- and p-type doped GaN layers.